213k views
2 votes
Solve the following system of equations:

6x – 3y + 10 = 0
2x + y + 9 = 0

User Dan Jagnow
by
6.0k points

1 Answer

6 votes
we have that
6x – 3y + 10 = 0 ----->equation 1
2x + y + 9 = 0-------> multiply by 3------> 6x+3y+27=0----> equation 2
add equations 1 and 2

6x – 3y + 10 = 0
6x+3y+27=0
----------------------
12x+37=0---------> 12x=-37-------> x=-37/12
substitute the value of x in the equation 1
6*(-37/12)-3y+10=0-----> -18.5-3y+10=0----> 3y=-8.5----> y=-8.5/3
x=-37/12-----> x=-3.08
y=--2.83

the answer is
x=-3.08
y=-2.83

see the attached figure
Solve the following system of equations: 6x – 3y + 10 = 0 2x + y + 9 = 0-example-1
User JBB
by
6.6k points